2006
DOI: 10.1097/01.aco.0000192777.09527.9e
|View full text |Cite
|
Sign up to set email alerts
|

An anesthesiologist's guide to hypoxic pulmonary vasoconstriction: implications for managing single-lung anesthesia and atelectasis

Abstract: An understanding of hypoxic pulmonary vasoconstriction is clinically relevant for anesthesiologists. Randomized clinical trials with robust endpoints are required to assess strategies for enhancing hypoxic pulmonary vasoconstriction in thoracic surgery patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 84 publications
(90 reference statements)
1
38
0
Order By: Relevance
“…HPV is critical to single-lung anesthesia for patients undergoing thoracic surgery such as lung tumor resections. 48 During these procedures, the patient is positioned on the side to facilitate surgical dissection, and single-lung ventilation is initiated using a doublelumen endobronchial tube (Fig 5A). During tube placement, the proximal and distal lumen tips are positioned above the carina and in the primary bronchus of the target lung, respectively (Fig 5B).…”
Section: Clinical Relevance Of Hpvmentioning
confidence: 99%
“…HPV is critical to single-lung anesthesia for patients undergoing thoracic surgery such as lung tumor resections. 48 During these procedures, the patient is positioned on the side to facilitate surgical dissection, and single-lung ventilation is initiated using a doublelumen endobronchial tube (Fig 5A). During tube placement, the proximal and distal lumen tips are positioned above the carina and in the primary bronchus of the target lung, respectively (Fig 5B).…”
Section: Clinical Relevance Of Hpvmentioning
confidence: 99%
“…Various factors are important in limiting shunt during OLA. These include HPV [20 ] that limits nonventilated lung shunt, administration of positive end-expiratory pressure (PEEP) to the dependent lung [21][22][23] and correct positioning of double lumen tubes [24]. A number of authors have demonstrated the benefit of dependent lung PEEP when titrated to restore functional residual capacity [21,22,25], whereas administration of predetermined [26] or excessive amounts of PEEP [22] does not always improve arterial oxygenation.…”
Section: Shunt Fractionmentioning
confidence: 99%
“…The effectivity of HPV is influenced by the lung volume. If the delivered tidal volumes and intrapulmonary pressures overstretch the ventilated alveoli, blood flow may be diverted to the nonventilated alveoli attenuating the HPV response and leading to increased V/Q mismatch and worsening hypoxemia (11).…”
Section: Discussionmentioning
confidence: 99%